2020
DOI: 10.1021/acs.jpcb.0c05319
|View full text |Cite
|
Sign up to set email alerts
|

On the Network Topology of Cross-Linked Acrylate Photopolymers: A Molecular Dynamics Case Study

Abstract: A reactive molecular dynamics approach is used to simulate cross-linking of acrylate polymer networks. By employing the same force field and reactive scheme and studying three representative multifunctional acrylate monomers, we isolate the importance of the nonreactive moieties within these model monomers. Analyses of reactive trajectories benchmark the estimated gel points, cyclomatic character, and spatially resolved cross-linking tendencies of the acrylates as a function of conversion. These insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 63 publications
6
18
0
Order By: Relevance
“…The degree of monomer conversion i.e., the fraction of bound functional groups as compared to the overall number of functional groups is an important parameter for polymerization reactions, especially in the DLW process. In polymer chemistry, it has been found that there is a saturation for monomer conversion as a function of the reaction time 41 . In the case of DLW, different authors reported different degrees of conversion for commercial and noncommercial photoresists 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of monomer conversion i.e., the fraction of bound functional groups as compared to the overall number of functional groups is an important parameter for polymerization reactions, especially in the DLW process. In polymer chemistry, it has been found that there is a saturation for monomer conversion as a function of the reaction time 41 . In the case of DLW, different authors reported different degrees of conversion for commercial and noncommercial photoresists 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 40 have used this approach in order to model continuous liquid interface production (CLIP) 3D printing technique aiming to investigate the effects of elastic, capillary, and friction forces on the quality of the shape of the 3D printed objects. Karnes et al 41 studied the cross-linking of acrylate polymer networks using a reactive MD simulation approach with an all-atom force field. Their study links the monomer conversion efficiency with macroscopic properties, e.g., gel point conversion, illustrating the ability of molecular mechanics as a useful tool in the rational design of photo-polymerized resins.…”
Section: Introductionmentioning
confidence: 99%
“…As the monomer and polymer concentrations depend on the degree of double-bond conversion and the monomer consumption dominates the reaction at the beginning of the polymerization (due to the entropic control of the reaction), the decision is made to calculate [M] and [P] as a linear function in an approximation of the findings from Karnes et al [70] of the double-bond concentration [N V ], yielding:…”
Section: Discussionmentioning
confidence: 99%
“…This will require tuning print parameters, such as light intensity and time of print, and incorporating computational simulations tools to study local material response. 71 Furthermore, incorporation of multiwavelength capabilities with VAM provides an exciting opportunity for complex multimaterial and high-resolution structure fabrication. 72,73 Multimaterial and multiwavelength VP…”
Section: Volumetric Additive Manufacturingmentioning
confidence: 99%